A river of stars : a novel - Hua, Vanessa (Ballantine Books, 2018)
"In a powerful debut novel about motherhood, immigration, and identity, a pregnant Chinese woman makes her way to California and stakes a claim to the American dream. Holed up with other moms-to-be in a secret maternity home in Los Angeles, Scarlett Chen is far from her native China, where she worked in a factory job and fell in love with the owner, Boss Yeung. Now she's carrying his baby. Already married with three daughters, he's overjoyed because the doctors confirmed he will finally have the son he has always wanted. To ensure that his son has every advantage, he has shipped Scarlett off to give birth on American soil. U.S. citizenship will open doors for their little prince. As Scarlett awaits the baby's arrival, she chokes down bitter medicinal stews and spars with her imperious housemates. The only one who fits in even less is Daisy, a spirited teenager and fellow unwed mother who is being kept apart from her American boyfriend. Then a new sonogram of Scarlett's baby reveals the unexpected. Panicked, she escapes by hijacking a van--only to discover that she has a stowaway: Daisy, who intends to track down the father of her child. They flee to San Francisco's bustling Chinatown, where Scarlett will join countless immigrants desperately trying to seize their piece of the American dream. What Scarlett doesn't know is that her baby's father is not far behind her. --